Stay Competitive in the Digital Age : The Future of Banks - Liu, Estelle (IMF Working Papers; Working Paper ;, 2021)
The latest advancement in financial technology has posed unprecedented challenges for incumbent banks. This paper analyzes the implications of these challenges on bank competitveness, and explores the factors that could support digital advancement in banks. The analysis shows that the traditionally leading role of banks in advancing financial technology has diminished in recent years, and suggests that onoing efforts to catch up to the digital frontier could lead to a more concentrated banking industry, as smaller and less tech-savvy banks struggle to survive. Cross-country evidence has suggested that banks in high-income economies appear to have been the digital leaders, likely benefiting from a sound digital infrastructure, a strong legal and business environment, and healthy competition. Nonetheless, some digital leaders may fall behind in the coming years in adopting newer technologies due to entrenched consumer behavior favoring older technologies, less active fintech and bigtech companies, and weak bank balance sheets.